J. Ambraziejus as Educator of National Self-Consciousness in Vilnius Region - Pruskus, Valdas (Problemos, 1991)
Activity and social views of Juozas Ambraziejus (1885-1915) are considered in the paper. Juozas Ambraziejus is said to represent a Catholic activist who took an active role in the fight against polonization and who called for national self-consciousness in Vilnius region. His conception of active patriotism is considered too. The rational organisation of economic activity is pointed to be the central element of the conception.